Pediatric Neuroborreliosis: Current Challenges in Diagnosis and Treatment of Lyme Disease - Sysło, Oliwia; Marszał, Wiktoria; Czyz , Sandra; Saracen, Nina (Journal of Education, Health and Sport, 2025)
Introduction and Objective: Lyme disease is an infection caused by Gram-negative, microaerophilic spirochetes of the Borrelia genus, transmitted to humans through the bite of an infected tick, which serves as the vector of this disease. It is one of the most frequently diagnosed tick-borne illnesses worldwide, with a rising incidence rate. Notably, children represent an increasingly affected population, emphasizing the need for focused attention on pediatric manifestations and management. Brief Overview of Current Knowledge - Lyme disease progresses through three clinical stages: early localized, early disseminated, and late stage. Each phase presents with characteristic clinical manifestations.  The early localized stage typically features erythema migrans, most often appearing on the scalp, neck, shoulders, legs, or lower back.  The early disseminated stage is marked by flu-like symptoms, lymphadenopathy, arthralgia, myalgia, cranial nerve palsies—most frequently involving the facial nerve (cranial nerve VII) —ocular involvement, and lymphocytic meningitis.  The late stage is characterized predominantly by pauciarticular arthritis, affecting large joints—especially the knees. In some cases, cardiac manifestations may occur, such as conduction abnormalities, myocarditis, or pericarditis. This progression underscores the multisystemic nature of Lyme disease and highlights the importance of early recognition and treatment to prevent long-term complications.